Aquatic macrophytes in morphological and physiological responses to the nanobubble technology application for water restoration - Wang, Shuo; Liu, Yunsi; Lyu, Tao; Pan, Gang; Li, Pan (American Chemical Society, 2020)
Nanobubble technology, as an emerging and sustainable approach, has been used for remediation of eutrophication. However, the influence of nanobubbles on the restoration of aquatic vegetation and the mechanisms are unclear. In this study, the effect of nanobubbles at different concentrations on the growth of Iris pseudacorus (Iris) and Echinodorus amazonicus (Echinodorus) was investigated. The results demonstrated that nanobubbles can enhance the delivery of oxygen to plants, while appropriate nanobubble levels will promote plant growth, excess nanobubbles could inhibit plant growth and photosynthesis. The nanobubble concentration thresholds for this switch from growth promotion to growth inhibition were 3.45 × 107 and 1.23 × 107 particles/mL for Iris and Echinodorus, respectively. Below the threshold, an increase in nanobubble concentration enhanced plant aerobic respiration and ROS generations in plants, resulting in superior plant growth. However, above the threshold, high nanobubble concentrations induced hyperoxia stress, particularly in submergent plants, which result in collapse of the antioxidant system and the inhibition of plant physiological activity. The expression of genes involved in modulating redox potential and the oxidative stress response, as well as the generation of relevant hormones, were also altered. Overall, this study provides an evidence-based strategy to guide the future application of nanobubble technology for sustainable management of natural waters.
Keywords: eutrophication control; floating-bed wetland; oxidant/antioxidant species; chlorophyll content; gene expression; hormone generation